2016
DOI: 10.1007/s12040-016-0694-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ionospheric characteristic parameters obtained by GPS and ionosonde with IRI model over China

Abstract: This paper presents a comparison of ionospheric characteristic parameters obtained by a GPS network and three ionosondes at Mohe (122.4 • E, 53.5 • N, dip angle 70.983 • N), Zuolingzhen (114.6 • E, 30.5 • N, dip angle 46.350 • N), and Fuke (109.1 • E, 19.5 • N, dip angle 27.083 • N) located in China with an IRI model in the year 2011. Observed NmF2 and hmF2 values at the three stations are compared with IRI2007 and IRI2012 predictions, respectively. The results show that there are clear linear correlations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Since IRI is a climatological model, it cannot provide TEC values with the high accuracy as GPS-TEC values. Many authors have reported evaluations of the IRI model over different areas of the world during periods of quiet or active space weather2425262728293031323334353637. The capabilities of and improvements to the IRI model have been shown, but there is not very good agreement between the IRI model predictions and the observed values, especially during periods of active space weather.…”
Section: Basic Methodology Of Global Vtec Modelingmentioning
confidence: 99%
“…Since IRI is a climatological model, it cannot provide TEC values with the high accuracy as GPS-TEC values. Many authors have reported evaluations of the IRI model over different areas of the world during periods of quiet or active space weather2425262728293031323334353637. The capabilities of and improvements to the IRI model have been shown, but there is not very good agreement between the IRI model predictions and the observed values, especially during periods of active space weather.…”
Section: Basic Methodology Of Global Vtec Modelingmentioning
confidence: 99%
“…Many scholars have investigated the accuracy of these models for different regions of the world during periods of different solar and geomagnetic activities (Abdu et al 1996;Araujo-Pradere et al 2003;Bertoni et al 2006;Lee and Reinisch 2006;Bhuyan and Borah 2007;Mosert et al 2007;Adewale et al 2011;Nigussie et al 2013;Okoh et al 2013;Olwendo et al 2013;Wichaipanich et al 2013;Wang 2016). The annual mean of the root-mean-square (RMS) of the differences between IGS GIMs and IRI predictions in 2014 was approximately 10 total electron content units (TECU, 10 16 el/m 2 ) .…”
Section: Introductionmentioning
confidence: 99%